Evaluation of the Environmental Chemistry Course Using the CIPP Model: Integrating SDGs and Enhancing Students' Environmental Literacy - Mellyzar, Mellyzar; Nahadi, Nahadi; Sriyati, Siti; Hernani, Hernani (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study evaluates the alignment of the curriculum with national policies and global environmental challenges, assesses the availability of resources and teaching strategies, and measures students' learning outcomes in cognitive, affective, and behavioral dimensions. Using a mixed-methods approach within the CIPP (Context, Input, Process, and Product) evaluation model, the study involved the program chair, two-course instructors, and 26 students from a public university in Aceh. Research instruments included questionnaires, observation sheets, interview guides, and test items. The findings indicate that the curriculum is relevant to global issues and supports the development of students' critical thinking skills. However, limited laboratory facilities, insufficient funding, and a lack of support for environment-based projects pose significant challenges to optimal curriculum implementation. Additionally, the program effectively enhances students' understanding of global environmental issues and their relevance to the SDGs but requires stronger integration of practical applications and explicit connections to SDG targets. Recommendations include project-based learning innovations, cross-sector collaborations, and improvements in facilities and funding to holistically enhance students' environmental literacy and prepare them as sustainability change agents.